2014
DOI: 10.1155/2014/421291
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin in Hemorrhagic Shock: A Systematic Review and Meta-Analysis of Randomized Animal Trials

Abstract: Objective. The latest European guidelines for the management of hemorrhagic shock suggest the use of vasopressors (norepinephrine) in order to restore an adequate mean arterial pressure when fluid resuscitation therapy fails to restore blood pressure. The administration of arginine vasopressin (AVP), or its analogue terlipressin, has been proposed as an alternative treatment in the early stages of hypovolemic shock. Design. A meta-analysis of randomized controlled animal trials. Participants. A total of 433 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 65 publications
0
31
0
1
Order By: Relevance
“…3 The current treatment of hemorrhagic shock is limited to fluid resuscitation, surgical/interventional bleeding control, and blood component substitution once the patient arrives in the hospital. Although pressure-support resuscitation of hemorrhagic shock has been discussed as a possible strategy to improve outcomes, 46 drugs that increase shock tolerance, stabilize cardiovascular function, and prolong survival are currently not available.…”
mentioning
confidence: 99%
“…3 The current treatment of hemorrhagic shock is limited to fluid resuscitation, surgical/interventional bleeding control, and blood component substitution once the patient arrives in the hospital. Although pressure-support resuscitation of hemorrhagic shock has been discussed as a possible strategy to improve outcomes, 46 drugs that increase shock tolerance, stabilize cardiovascular function, and prolong survival are currently not available.…”
mentioning
confidence: 99%
“…The question then arises whether the intra-operative use of vasopressin may also decrease blood loss in patients without portal hypertension undergoing liver resection surgery for metastases. 22,23 We have previously shown that intraoperative nitroglycerine infusion effectively lowers the portal, hepatic and central venous pressures. On the other hand, if the major determinant of bleeding in liver resection surgery is the filling volume of the intra-hepatic capacitance vessels and/or transhepatic blood flow, then vasopressin could potentially decrease bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…During the early phase of haemorrhagic shock, BP is maintained by sympathetic activation, leading to arterial and compensatory venous vasoconstriction 6 7. When a large amount of blood is lost, this mechanism becomes less effective, leading to vasoplegia of organs.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin inhibits vasodilator mechanisms that contribute to hypotension and vascular hyporeactivity in the late phase of haemorrhagic shock. There is no recommended ceiling dose of vasopressin in humans 7. But typically doses did not exceed 2–4 U/hour to counter vasodilatory shock.…”
Section: Discussionmentioning
confidence: 99%